The Impact of Zakat on Economic Growth in 5 State in Indonesia - Suprayitno, Eko (International Journal of Islamic Banking and Finance Research, 2020)
This study aims to reveal the impact of zakat distribution on macroeconomic in 5 state In Indonesia, by using ECM analysis. The motivation of the current research lies on the belief of a large number of economists that zakat does not affect macro economy because 2.5 percent is perceived insignificant. This issue leads to a high curiosity about the impact of zakat distribution in Indonesia. This study finds that zakat has a significant and positive relationship with economic growth. The results of the ECM analysis show that the distribution of zakat positively influences on economic growth. The long-run elasticity of zakat variable is positive and significant.